Analysis of Holland Theory Career Guidance in Student Career Planning - Erfan Ramadhani; Ana Tul Jannah; Ramtia Darma Putri (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2020)
The problem of this research is based on the large number of students entering high school on the wishes of parents, students feel wrongly entering the department because it is not in accordance with their talents, interests and potential. Furthermore, efforts have been made by the teacher for guidance and counseling in providing Holland theory career guidance services. The research method used is descriptive qualitative. The informants in this study were counseling teachers and students. Data analysis in this research uses steps of data reduction, data presentation, and verification. The results of this study indicate that the implementation of Holland's theory career guidance services has been going well. From the results of interviews, observations and documentation to research informants regarding the implementation of Holland theory career guidance services, it can be understood that at the planning, implementation, evaluation and follow-up stages have been going well as they should, this is evident in the existence of service program plans, materials and instruments Holland, as well as the results of the Holland instrument analysis of students who already know the personality type and direction of their career choices.